2014
DOI: 10.1002/anie.201405455
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (+)‐Discodermolide by Catalytic Stereoselective Borylation Reactions

Abstract: The marine natural product (+)-discodermolide was first isolated in 1990 and, to this day, remains a compelling synthesis target. Not only does the compound possess fascinating biological activity, but it also presents an opportunity to test current methods for chemical synthesis and provides a forum for the inspiration of new reaction development. In this manuscript, we present a synthesis of discodermolide that employs a previously undisclosed stereoselective catalytic diene hydroboration and also establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 57 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…The transfer of an allyl group to an aldehyde is an important method to afford synthetically versatile homoallylic alcohols . While this transformation can be carried out with several types of allylmetal species, the synthetic accessibility, tunability, and predictable stereochemical reaction outcomes provided by allyl boron species have contributed to the popularity of this class of reagent . Substituted allylboranes of defined Z ‐ or E ‐double bond geometry (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transfer of an allyl group to an aldehyde is an important method to afford synthetically versatile homoallylic alcohols . While this transformation can be carried out with several types of allylmetal species, the synthetic accessibility, tunability, and predictable stereochemical reaction outcomes provided by allyl boron species have contributed to the popularity of this class of reagent . Substituted allylboranes of defined Z ‐ or E ‐double bond geometry (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] While this transformation can be carried out with several types of allylmetal species,t he synthetic accessibility, tunability,and predictable stereochemical reaction outcomes provided by allyl boron species have contributed to the popularity of this class of reagent. [3][4][5][6] Substituted allylboranes of defined Z-orE-double bond geometry (e.g.crotyl boranes) translate to a syn-o ranti-relationship,r espectively,b etween the two newly formed stereocenters. [7] Theh igh diastereoselectivity observed is the result of aclosed chair-like transition state,the assembly of which is governed by the steric demand of the reaction partners.S everal enantioselective variants have been reported that employ chiral auxiliaries,reagents,or catalysts.…”
mentioning
confidence: 99%
“…37 Two asymmetric hydroformylation reactions were utilized in the synthesis of the marine natural compound (+)discodermolide (62) that was developed by Morken and coworkers (Scheme 11). 38 This polyketide, which was isolated in 1990, 39 is a highly complex attractive synthetic subject possessing a considerably promising biological activity. 40 Thus, this molecule became a compelling target of the pharmaceutical industry, as evidenced by numerous studies towards its large-scale synthesis.…”
Section: Syn Thesismentioning
confidence: 99%
“…Straightforward routes to prepare rottnestol and herboxidine have been developed involving stereoselective preparation of organoboron intermediates through catalytic, multicomponent, gram‐scale processes . Stereoselective borylations have opened alternative access to complex compounds such as (+)‐discodermolide, ( S )‐fluoxetine, ( S )‐duloxetine, (−)‐filiformin, (+)‐giganin and its C10 epimer, hydroxyphthioceranic acid, as well as the mating hormone α1 of the virulent plant pathogen Phytophthora , which are the most representative examples within the last years.…”
Section: Introductionmentioning
confidence: 99%